IL-9 and its receptor are predominantly involved in the pathogenesis of UC. Issue 5 (23rd June 2014) - Nalleweg, Nancy; Chiriac, Mircea Teodor; Podstawa, Eva; Lehmann, Christian; Rau, Tilman T; Atreya, Raja; Krauss, Ekaterina; Hundorfean, Gheorghe; Fichtner-Feigl, Stefan; Hartmann, Arndt; Becker, Christoph; Mudter, Jonas
Abstract : Objective: Several pathogenic roles attributed over the past two decades to either T helper (Th)1 or Th2 cells are increasingly becoming associated with interleukin (IL)-17 and most recently IL-9 signalling. However, the implication of IL-9 in IBD has not been addressed so far. Design: We investigated the expression of IL-9 and IL-9R by using peripheral blood, biopsies and surgical samples. We addressed the functional role of IL-9 signalling by analysis of downstream effector proteins. Using Caco-2 cell monolayers we followed the effect of IL-9 on wound healing. Results: IL-9 mRNA expression was significantly increased in inflamed samples from patients with UC as compared with controls. CD3 + T cells were major IL-9-expressing cells and some polymorphonuclear leucocytes (PMN) also expressed IL-9. IL-9 was co-localised with the key Th9 transcription factors interferon regulatory factor 4 and PU.1. Systemically, IL-9 was abundantly produced by activated peripheral blood lymphocytes, whereas its receptor was overexpressed on gut resident and circulating PMN. IL-9 stimulation of the latter induced IL-8 production in a dose-dependent manner and rendered PMN resistant to apoptosis suggesting a functional role for IL-9R signalling in the propagation of gut inflammation. Furthermore, IL-9R was overexpressed on gut epithelial cells and IL-9 induced STAT5 activation in these cells. Moreover, IL-9 inhibited the growth of Caco-2 epithelial cell monolayers in wound healing experiments. Conclusions: Our results provide evidence that IL-9 is predominantly involved in the pathogenesis of UC suggesting that targeting IL-9 might become a therapeutic option for patients with UC.